Enhancing a bank's competitive advantage through the integration of TQM practices, Entrepreneurial Orientation (EO), and Organizational Culture - Al-Swidi, A.K.; Mahmood, Rosli (2011)
In the current changing business environment, banks, among other organizations, are required not only to create their competitive advantage to lead the trend, but also to be able to sustain and upgrade the created competitive advantage. However, throughout this paper, the researchers tried to review the literature of TQM, Entrepreneurial Orientation (EO), and Organizational Culture (OC) through deeply investigating how these management practices contribute to the creation of banks competitive advantage. In the relevant literature, there have been enormous studies exploring the effect of TQM, EO on the overall organizational performance. Other studies; however, tried to include the effect of OC to explain the variance in the organizational performance. But unfortunately studying these relationships in the banking sector has been greatly neglected. Moreover, the integration of these three constructs has been academically neglected. Therefore, this paper is expected to contribute to that by developing a conceptual model that hypothesizes the existence and significance of these relationships. These hypotheses can be further validated and empirically examined as a future research suggestion.